Analisis Kritis Terhadap Kebijakan Standar Kompetensi Pendidik Dan Tenaga Kependidikan Di Lembaga Pendidikan Islam Swasta - Fitri, Fajar Laelatul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
One aspect that can be seen from the achievement of educational goals in Indonesia is the educators. If Islamic schools have competent educators, it will have implications for the intelligence of the nation with good intellectual abilities. This research aims to analyze the extent of the role of teacher competency standard policies so that the nation's goals can be achieved, therefore the creation of educator standards and education personnel in Islamic educational institutions. The research method used is a literature study by collecting various sources and literature related to the laws used by Islamic educational institutions in accordance with the problems studied. From the results of the analysis, 4 competency standards were obtained that are mandatory by educators, namely (1) social competence, (2) pedagogic competence, (3) professional competence, and (4) personality competence.